2017
DOI: 10.1103/physreve.95.052602
|View full text |Cite
|
Sign up to set email alerts
|

Fluidization and wall slip of soft glassy materials by controlled surface roughness

Abstract: The motion of soft-glassy materials (SGM) in a confined geometry is strongly impacted by surface roughness. However, the effect of the spatial distribution of the roughness remains poorly understood from a more quantitative viewpoint. Here we present a comprehensive study of concentrated emulsions flowing in microfluidic channels, one wall of which is patterned with micron-size equally spaced grooves oriented perpendicularly to the flow direction. We show that roughness-induced fluidization can be quantitative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…The values of the cooperativity scale ξ extracted from the model [41,47,48] are in agreement with experimental observations [7,49]. Recently, the model has been used in synergy with experiments on real emulsions in order to quantify the impact of the fluidization induced by the roughness of microchannels on the flow behavior of the emulsion [47,48]. As shown in the reminder of the paper, for this "model emulsion" the static and dynamic yield-stress values are found to differ.…”
Section: Modelsupporting
confidence: 78%
“…The values of the cooperativity scale ξ extracted from the model [41,47,48] are in agreement with experimental observations [7,49]. Recently, the model has been used in synergy with experiments on real emulsions in order to quantify the impact of the fluidization induced by the roughness of microchannels on the flow behavior of the emulsion [47,48]. As shown in the reminder of the paper, for this "model emulsion" the static and dynamic yield-stress values are found to differ.…”
Section: Modelsupporting
confidence: 78%
“…Several experimental studies have reported results in the direction that rough surfaces affect surface fluidization in confined flows (Goyon et al 2008;Goyon et al 2010;Mansard et al 2014;Geraud et al 2013). A recent study analyzes the importance of surface texture with respect to surface fluidization by changing the amplitude and wavelength of the corrugations created by specific surface patterns (Derzsi et al 2016). Still more surprising significant alterations of the velocity profiles over distances to the wall much larger than a few particle sizes have been reported when surfaces are smooth and develop attractive interactions with the particles of the dispersions (Seth et al 2012;Paredes et al 2015).…”
Section: Non Locality Mediated By Surface Roughnessmentioning
confidence: 99%
“…The detailed impact of surface roughness or surface interaction between the fluid and the solid has been studied through detailed measurements of the flow characteristics at a local scale, by few authors [38][39][40], in the yielding regime.…”
Section: Impact Of Surface Characteristicsmentioning
confidence: 99%